Community Disaster Resilience and the Rural Resilience Index. (February 2015) - Cox, Robin S.; Hamlen, Marti
This article describes the development and field testing of the Rural Resilience Index (RRI), an applied disaster resilience assessment index for use in rural and remote communities. The index was generated as part of the Rural Disaster Resilience Project. This community-centered action research project was designed to respond to the global emphasis on increasing the capacity of all communities, large and small, to meet the growing challenge of disasters, climate change, and other threats. The goals of the project were to produce resilience assessment and planning tools that could be used by communities to generate locally relevant data on their current resilience and be able to monitor and enhance their resilience over time. This article describes the development and field testing of the RRI, which is designed as a user-friendly, process-based, qualitative resilience assessment tool. The RRI emphasizes the value of citizen engagement in resilience planning and a whole-of-community approach to resilience addressing issues such as the quality and availability of local resources, expertise, skills, and services; governance issues; economic and employment issues; culture; disaster preparedness; and emergency management planning.